The Effectiveness Of Facial Massage On Reducing Sleep Disorders (Insomnia) In The Elderly In Tohudan Village, Karanganyar - Ramadanti, Aulia Sri; Wahyu Widiarti, Afrianti; Triyana, Triyana (Poltekkes Kemenkes Surakarta, 2024)
Background: Insomnia is a disorder in which sufferers experience difficulty initiating and maintaining sleep so that they cannot adequately maintain their sleep needs, both in quality and quantity. In this study, physiotherapy efforts to reduce insomnia used facial massage intervention as measured by the insomnia severity index (ISI). Objective: To determine the effect of facial massage on reducing the scale of sleep disorders (insomnia) in pre-elderly people in Tohudan village, Karanganyar regency. Methods: The method used in this research is quasi-experimental, with the design used being one group pre-test and post-test. From the population of 200 elderly in Senden, Tohudan village, and 72 elderly came to Posyandu Lansia, 19 people who met the inclusion criteria using a purposive sampling method would be given treatment in the form of facial massage for 3 consecutive days. Pre- and post-test measurements were carried out by filling out the ISI scale questionnaire. Results: The pre- and post-test differences were carried out using the paired t-test and obtained a p-value of 0.000 (p<0.05). So the alternative hypothesis (Ha) in this study is accepted. Conclusion: Giving facial massages reduces insomnia in elderly people in Tohudan Village.